Dirac Fermions in Half‐Metallic Ferromagnetic Mixed Cr1−xMxPSe3 Monolayers. Issue 12 (6th November 2020) - Yang, Juntao; Zhou, Yong; Dedkov, Yuriy; Voloshina, Elena
Abstract: The electronic and magnetic properties of pristine CrPSe3 and mixed Cr 1 − x M x PSe3 (M = Zn, Cd, Hg) monolayers are studied using density functional theory including an on‐site Coulomb term (density functional theory (DFT) + U ) and tight‐binding approach. While pristine CrPSe3 monolayer has an antiferromagnetic ground state, its alloying with MPSe3 may give rise to half‐metallic ferromagnet with high Curie temperature. The resulting monolayers demonstrate single‐spin Dirac cones of mainly Cr‐ d character located in the first Brillouin zone directly at the Fermi energy. The calculated Fermi velocities of Dirac fermions indicate very high mobility in mixed Cr 1 − x M x PSe3 monolayers, that makes this material appealing for low‐dimensional spintronics applications. Abstract : Recent progress in low‐dimensional magnetism and spintronics is connected to the discovery of novel 2D materials. Using density functional theory, the stabilization of the new 2D materials is predicted. These layered two‐atom transition metal trichalcogenides demonstrate Dirac‐electron half‐metallic ferromagnetic behavior with high Curie temperature, which makes them promising for future spintronics applications.